Finite Element Approach for Coupled Striplines Embedded in Dielectric Material - Sarhan M. Musa; Matthew N.O. Sadiku (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
In this paper, we present finite element method (FEM) to investigate the quasi-static analysis of two dimensional (2D) shielded two coupled stripline structures for microelectronic devices. In the proposed method, we specifically determine the values of capacitance per unit length and inductance per unit length of shielded two vertically coupled striplines and shielded two coupled striplines embedded in dielectric material. Extensive simulation results are presented, and some comparative results are given by other methods and found them to be in excellent agreement. Furthermore, we determine the quasi-TEM spectral for the potential distribution of these shielded two coupled striplines.